Advances in 3D Printing - Sharma, Ashutosh (IntechOpen, 2023)
Advances in 3D Printing presents an overview of various types of advances in 3D printing. It discusses current research trends, problems, and applications of 3D printing processes and materials. The book also discusses advances in bioprinting, tissue generation, radiotherapy, and safety issues in health care. It showcases applications of 3D printing in digital design, body part surrogates, rheological models, airway stents, 3D-printed cermets, and more. It also discusses advances in biomimetic nanocomposite materials, intellectual property concerns, and safety issues in 3D printing technology.